Social Media Dependence and Self-Esteem Among College Students of Bestlink College of the Phillippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
In recent years, there has been a significant increase in social media usage, especially in thenew generation, as people spend more time online maintaining connectivity when face-to-facecommunication is limited.The result showed that the majority of the respondents' ages ranged from 21 to 23 years old,mostly female. The researchers used quantitative data that answered the overall weightedmean level of self-esteem and social media addiction. As for Inflated self-esteem, the overallmean was 2.80; Low self-esteem got an overall mean of 2.74, while the highest variable, Highself-esteem, got 3.98. The overall weighted mean of social media dependence was 3.02.Lastly, there was a weak relationship between social media dependence and self-esteemamong college students of Bestlink College of the Philippines (r = - 0.45, p>0.05).Analysis showed that college students used social media for gratification to experientialthings, whether it's a negative or positive situation, and did not intend to use it excessively.The researchers recommend that students learn to build their self-identity and self-esteemwithout depending on what they see on social media. Moreover, users of social media shouldconsider that excessive use of social media can lead to addiction.
Keywords: Social Sciences